Program dan Peran Guru Bahasa Indonesia sebagai Penunjang Prestasi dan Karakter Siswa - Tika Afrilla; Yaya Sunarya (Universitas Indraprasta PGRI, 2023)
This research was conducted with the aim of knowing academic and non-academic programs, the role of Indonesian language teachers in supporting student achievement and character as well as the implementation of the school literacy movement at Teladan 1 High School Yogyakarta. This study used a qualitative descriptive method, data collection techniques were carried out through interviews. The subjects in this study were 2 Indonesian language teachers and the vice principal of student affairs at SMAN 1 Yogyakarta. Data analysis techniques consist of data reduction, data presentation, and drawing conclusions. the research results obtained that school institutions play an important role in fostering interests, talents and skills through academic and academic programs. SMAN 1 Yogyakarta really accommodates its students in developing and achieving achievements. In addition, the teacher's role is quite large in motivating students, supporting achievement and character through learning Indonesian, the teacher is able to develop teaching materials, learning media, learning methods that are able to shed enthusiasm and be active in students, one of which is by giving students the freedom to find learning resources and based learning. class discussions, in addition to utilizing technology in learning. The method used to motivate is quite diverse, one of which is presenting the work of student teachers so that students are inspired to engage in creative writing and by giving appreciation to student work. In supporting student character, it can be through cultural and literary studies, as well as studying values, norms, behaviors contained in literary works in order to develop students' character with noble character in accordance with national culture. Apart from that, SMAN 1 Yogyakarta remains consistent with the school literacy movement which is implemented in various school activities such as outdoor studies which involve writing essays and camps which involve writing poetry. This is one way for schools to support student achievement who are smart, critical, innovative, critical and creative.Keywords: chool program, role of teacher, student achievement, school literacy movement